(untitled) (Eurasian Research Bulletin, 2023)
This article talks about the methods of teaching visual and decorative-practical art in harmony. Based on pedagogical data, the author analyzed the problem on the basis of existing scientific literature and studied the existing specific aspects of the methods of teaching visual and decorative-practical art in harmony.